PERKEMBANGAN MUSLIM CHAMPA - Sayuti; Ade Irma; Zulkifli (SADIDA, 2023)
Abstract: The ups and downs of the development of Islam in Vietnam is the background of this paper. Based on history, Islam has long been rooted in Vietnam, but until now Islam is still being adopted by the Vietnamese government. Therefore the author wants to examine how the development of Islam in Vietnam? The research method is qualitative with content analysis techniques on issues related to Vietnam circulating in online media portals and literature reviews (books, scientific journals). In 1986 the life of Muslims in Vietnam began to improve since the Socialist Government began constructing the Doi Moi (Renovation) policy which allowed Muslims to organize themselves in Vietnam, worship in surau, and madrasas were allowed to teach Islamic religion. But the fact is that there are still inconveniences in worship because the Vietnamese police are still secretly monitoring religious activities in places of worship (mosques), Islamic education and Islamic understanding are prohibited in public education, nor is it justified to establish religious schools. This condition shows that the freedom of Muslims in Vietnam is not intact. The convenience of worship, if it is still in an atmosphere of surveillance, will certainly make the Muslim community there afraid and a sense of mutual suspicion will arise, both among the community and between government officials. The Cham Muslim community is still having a hard time getting a job in their country, especially elite jobs or the private sector and government. The challenge of Muslims is a factor that influences the dynamics of Islamic development in Champa. Keywords: Vietnamese, Islamic, Champa Abstrak: Situasi naik turunnya perkembangan Islam di Vietnam menjadi latar tulisan ini. Berdasarkan sejarah, Islam telah lama mengakar di Vietnam, namun hingga saat ini Islam masih di anak tirikan oleh pemerintah Vietnam. Karenanya penulis ingin mengkaji bagaimana perkembangan Islam di Vietnam? Melalui penelitian terdahulu yang dilakukan di Vietnam dan pemberitaan media online. Metode penelitian adalah kualitatif dengan teknik content analysis (analisis content) tentang isu-isu berkaitan dengan Vietnam yang beredar di portal media secara online serta literatur review (buku, jurnal imiah). Tahun 1986 kehidupan warga Islam di Vietnam mulai membaik sejak Pemerintah Sosialis mulai mengkonstruksi kebijakan Doi Moi (Renovasi) yang membolehkan umat Islam untuk mengorganisasikan diri ke Vietnam, beribadah di surau, dan madrasah sudah dibolehkan memberikan pelajaran agama islam. Namun faktanya masih terdapat ketidaknyamanan beribadah karena polisi Vietnam masih diam-diam mengawasi kegiatan keagamaan di tempat ibadah (masjid), pendidikan Islam dan pemahaman Islam dalam pendidikan umum dilarang, dan sekolah agama tidak diperbolehkan. Kondisi ini menunjukkan kebebasan umat muslim di Vietnam belum utuh. Kenyamanan beribadah, jika masih dalam suasana pengawasan pastinya membuat masyarakat muslim disana takut dan timbul rasa saling curiga baik antar masyarakat ataupun antar aparat pemerintah. Masyarakat muslim Cham masih sulit mendapatkan pekerjaan di negaranya, lebih-lebih pekerjaan yang elit atau sektor private dan pemerintahan. Tantangan umat Islam ini menjadi faktor yang mempengaruhi dinamika perkembangan Islam di Champa.